Mr. Gottlieb on Marx: A Comment - Meek, Ronald L. (Review of Economic Studies, 1952)
Journal Article Mr. Gottlieb on Marx: A Comment Get access Ronald L. Meek Ronald L. Meek Glasgow Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 20, Issue 1, 1952, Pages 78–83, https://doi.org/10.2307/2296164 Published: 01 January 1952